Histone deacetylase 8 inhibition prevents the progression of peritoneal fibrosis by counteracting the epithelial-mesenchymal transition and blockade of M2 macrophage polarization - Zhou, Xun; Chen, Hui; Shi, Yingfeng; Li, Jinqing; Ma, Xiaoyan; Du, Lin; Hu, Yan; Tao, Min; Zhong, Qin; Yan, Danying; Zhuang, Shougang; Liu, Na (Frontiers in Immunology, 2023)
Peritoneal dialysis (PD) is an effective replacement therapy for end-stage renal disease patients. However, long-term exposure to peritoneal dialysate will lead to the development of peritoneal fibrosis. Epigenetics has been shown to play an important role in peritoneal fibrosis, but the role of histone deacetylases 8 (HDAC8) in peritoneal fibrosis have not been elucidated. Here, we found that HDAC8 expressed highly in the peritoneum from patients with PD-related peritonitis. We further revealed that the level of HDAC8 in the dialysate increased over time, and HDAC8 was positively correlated with transforming growth factor-β1 (TGF-β1) and vascular endothelial growth factor (VEGF), and negatively correlated with cancer antigen 125. In mouse model of peritoneal fibrosis induced by high glucose dialysate, administration of PCI-34051 (a selective HDAC8 inhibitor) significantly prevented the progression of peritoneal fibrosis. Treatment with PCI-34051 blocked the phosphorylation of epidermal growth factor receptor (EGFR) and the activation of its downstream signaling pathways ERK1/2 and STAT3/HIF-1α. Inhibition of HDAC8 also reduced apoptosis. In vitro, HDAC8 silencing with PCI-34051 or siRNA inhibited TGF-β1-induced epithelial-mesenchymal transition (EMT) and apoptosis in human peritoneal mesothelial cells (HPMCs). In addition, continuous high glucose dialysate or IL-4 stimulation induced M2 macrophage polarization. Blockade of HDAC8 reduced M2 macrophage polarization by inhibiting the activation of STAT6 and PI3K/Akt signaling pathways. In conclusion, our study revealed that HDAC8 promoted the EMT of HPMCs via EGFR/ERK1/2/STAT3/HIF-1α, induced M2 macrophage polarization via STAT6 and PI3K/Akt signaling pathways, and ultimately accelerated the process of peritoneal fibrosis.